EKONOMI POLITIK PENGEMBANG GAME LOKAL: Spasialisasi dan Ekspansi Bisnis PT Git Solution dan Noobzilla di Yogyakarta - Wahyuono, Jusuf Ariz (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2019)
This research highlights the dynamics of the development of the gaming industry in Yogyakarta. This study uses a political economy approach and will focus on one aspect of the political economy in Vincent Mosco's perspective, spatialization. The findings of the study found that the two-game developers in Yogyakarta had different characteristics, both resources, to ways to gain profits. This difference determines each developer to expand their business. PT GIT Solution expanded its business by forming GIT ALLIANCE, while Noobzilla grew its business by creating products (games) that were easier to port. The role of government in the game industry nationally and locally showed by BEKRAF and JDV. Even so, this role is considered not optimal in shaping the ecosystem of the gaming industry. This phenomenon is indicated by the support that is not comprehensive to other sectors (e.g., publishers). There is a lack of specific regulations related to the gaming industry that support the development of the local gaming industry. To cite this article (7th APA style): Wahyuono, J. A. (2019). Ekonomi Politik Pengembang Game Lokal: Spasialisasi dan Ekspansi Bisnis PT Git Solution dan Noobzilla di Yogyakarta [The Political Economy of Local Game Developer]. Journal Communication Spectrum, 9(2), 125-142. http://dx.doi.org/10.36782/jcs.v9i2.1954